PERFORMANCE FEATURES LABOR IN THE SPHERE OF TOURISM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the development of the tourism industry is directly related to the need to increase labor productivity in the industry and improve the efficiency of the use of human resources